Building Authentic Connection in the Patient-Physician Relationship - Sheryl Fuehrer; Amy Weil; Lars G. Osterberg; Donna M. Zulman; Matthew R. Meunier; Rachel Schwartz (SAGE Publishing, 2024)
Introduction/Objectives: Delivering optimal patient care is impacted by a physician's ability to build trusting relationships with patients. Identifying techniques for rapport building is important for promoting patient-physician collaboration and improved patient outcomes. This study sought to characterize the approaches highly skilled primary care physicians (PCPs) use to effectively connect with diverse patients. Methods: Using an inductive thematic analysis approach, we analyzed semi-structured interview transcripts with 10 PCPs identified by leadership and/or colleagues for having exceptional patient communication skills. PCPs practiced in 3 diverse clinic settings: (1) academic medical center, (2) Veterans Affairs clinic, and (3) safety-net community clinic. Results and Conclusions: The thematic analysis yielded 5 themes that enable physicians to establish connections with patients: Respect for the Patient, Engaged Curiosity, Focused Listening, Mutual Participation, and Self-Awareness. Underlying all of these themes was a quality of authenticity, or a state of symmetry between one's internal experience and external words and actions. Adopting these communication techniques while allowing for adaptability in order to remain authentic in one's interactions with patients may facilitate improved connection and trust with patients. Encouraging physician authenticity in the patient-physician relationship supports a shift toward relationship-centered care. Additional medical education training is needed to facilitate authentic connection between physicians and patients.